2022
DOI: 10.3390/foods11172642
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genotype and Environment on Food-Related Traits of Organic Winter Naked Barleys

Abstract: This study aimed to understand how genetics and environment influence organic winter naked barley composition and functionality, and to identify traits that might effectively categorize basic physicochemical functionality of food barley. Across three years, two locations, and 15 genotypes, genotype significantly influenced all 10 food-related traits and was the dominant influence for three. Location significantly influenced eight traits and was dominant for three. Year significantly influenced all traits but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Recognizing that statistical comparisons are not possible due to a lack of replication, there are notable differences between varieties in terms of total carbohydrates, total proteins, calcium, potassium, and sodium. Organic naked barley grain composition is known to be influenced by genotype, location, crop year, and crop year/location interactions ( Bunting et al, 2022 ). Because we used commercial varieties that were grown in different locations and in different seasons (fall vs spring-planted), we cannot determine if these nutritional differences are due to genotypic, environmental, or interaction effects.…”
Section: Resultsmentioning
confidence: 99%
“…Recognizing that statistical comparisons are not possible due to a lack of replication, there are notable differences between varieties in terms of total carbohydrates, total proteins, calcium, potassium, and sodium. Organic naked barley grain composition is known to be influenced by genotype, location, crop year, and crop year/location interactions ( Bunting et al, 2022 ). Because we used commercial varieties that were grown in different locations and in different seasons (fall vs spring-planted), we cannot determine if these nutritional differences are due to genotypic, environmental, or interaction effects.…”
Section: Resultsmentioning
confidence: 99%
“…All previous lines have been selected under conventional growing conditions. Specific food quality traits of the OR and NY trials are characterized by Bunting et al (2022).…”
Section: Methodsmentioning
confidence: 99%
“…Genotypes evaluated in NY that had high PHS included 10_0655, 10_0662, DH140490, and DH140394. To test for food quality, Bunting et al (2022) ran a preliminary Rapid Visco Analyzer test (RVA) for this trial grown in the NY and OR environments to evaluate samples for PHS before analyzing for food quality. They found that genotypes 10_0662, 10_0655, DH140490, and DH140394 had indications of PHS, which was consistent with PHS scoring in NY.…”
Section: Crop Sciencementioning
confidence: 99%